Association between lactate-to-albumin ratio and mortality in hepatic failure: a retrospective cohort study - Huan Wu; Long Wu; Li Luo; Hai-yang Li; Bao-fang Zhang (BMC Infectious Diseases)
Abstract Background Liver failure has a high mortality rate, and currently, there is no convenient risk predictor. The lactate-to-albumin ratio (LAR) has emerged as a promising predictor in various critical illnesses. However, its potential role in predicting all-cause mortality in patients with liver failure remains unexplored. Therefore, this study aims to investigate the correlation between LAR and all-cause mortality in patients suffering from liver failure. Methods We retrospectively analyzed data from patients with liver failure who were admitted to the intensive care unit (ICU) between 2008 and 2019, which were gathered from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. LAR was calculated from the ratio obtained from the first measurement taken within 24 h of admission. The optimal LAR threshold was determined using the Youden index. With LAR categorized into low, middle, and high groups based on tertiles, Kaplan - Meier analysis was employed to compare mortality risks among three patient groups. Multivariate Cox proportional hazards regression models were utilized to evaluate the association between LAR and all-cause mortality in hepatic failure patients within hospital admission. Additionally, receiver operating characteristic (ROC) and smoothing curve analysis were used to assess the predictive ability, sensitivity, and specificity of LAR for all-cause mortality in patients with liver failure, and the area under the curve (AUC) was calculated. A smooth curve fitting approach and threshold effect analysis were employed to detect the potentially non-linear relationship between the LAR and the risk of all-cause mortality in patients with hepatic failure. Finally, subgroup analyses were performed to assess the relationship between LAR and prognosis across different types of liver failure. Results A total of 902 patients with hepatic failure were included in this study. They were divided into survivors group (611 patients) and non-survivors group (291 patients) according to whether they survived during hospitalization, and the mortality rate of patients was 32.26%. The Kaplan-Meier survival curves illustrating patients in hepatic failure with elevated LAR showed a significantly heightened risk of in-hospital mortality (P < 0.001). We identified a non-linear relationship between LAR and the risk of hospital mortality after adjusting for potential confounders and the inflection point of LAR to be 1.33. LAR was shown to be an independent predictor of all-cause mortality within hospitalization in patients with hepatic failure by multivariate COX regression analysis (HR, 1.66; 95% CI, 1.35–2.05; P < 0.0001). The optimal cutoff value for separating the survival and death groups according to ROC was found to be 0.97. The AUC value for LAR was 0.755 (95% CI: 0.721, 0.789), which was higher than that for arterial blood lactate (AUC = 0.725) and serum albumin (AUC = 0.680) alone. It was not inferior even when compared to MELD (AUC = 0.677). Conclusion LAR has demonstrated good predictive value for all-cause mortality among liver failure patients in our retrospective study.